Penny Wise and Pound Foolish: Does Striving to Meet Earnings Expectations by Manipulating Real Activities Trigger Product Recalls? - Chen, Yangyang; Ma, Lijun; Pittman, Jeffrey; Yang, Xin (Management Science, 2025)
We examine whether managers’ activities in striving to reach earnings targets through real earnings manipulation affect their firms’ product recalls. Our evidence implies that firms suspected of manipulating real activities in trying to meet earnings benchmarks exhibit a higher likelihood and frequency of product recalls. In cross-sectional results consistent with expectations, we find that the impact of exploiting real activities to attain earnings benchmarks on product recalls intensifies for firms whose managers have stronger incentives to manage earnings and subsides for firms subject to greater customer power and firms with more growth opportunities. Additional analysis shows that lowering product quality to meet or beat earnings expectations undermines firms’ future performance. This paper was accepted by Ranjani Krishnan, accounting. Funding: Y. Chen acknowledges the General Research Fund of the Research Grants Council of Hong Kong [Project 15504219] for financial support. L. Ma acknowledges financial support from the Ministry of Education Project of Humanities and Social Sciences [Project 22YJC630099] and the Young Scholars Grant Program of the University of International Business and Economics [Project 20YQ06]. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2021.04035 .